Estudio de factibilidad para la creación de un conservatorio de música cristiana, cantón Quevedo, año 2015 - Gómez Araujo, Roxana Vianey (2015)
The present project consists on the creation of Christian music's conservatory, since a company doesn't exist with this characteristics in the City of Quevedo. For the development of the investigation work the economically active population took in the 2010, of the Canton Quevedo that has a total 173.575 inhabitants according to the National Institute of Statistical and Censuses (INEC), the formula of probabilities was applied to calculate the populational sample, which gave a total of 399 people, to those that are applied the survey to gather the necessary information for the elaboration of the project. According to the market study, thanks to the obtained results of the survey carried out the inhabitants of the Canton Quevedo, one could notice that 73% of those interviewed agrees with the creation of Christian music's conservatory, in such a way that an unsatisfied demand is observed, since a company that offers this service doesn't exist. With the technical study the location of the company was determined, where 80% of those interviewed pointed out that the appropriate place so that Christian music's conservatory works it is in downtown. The financial study determined the necessary investment for the realization of the project, which is of 85.000,00, the one which that it will be financed by 9% of own Capital while 91% will be financed by the National Bank of Development (BNF) that is to say that $77,000.00 will be financed by the bank with an interest rate from 11 annual% to four years Term.